2006
DOI: 10.1111/j.1744-313x.2006.00638.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing‐based analysis of the HLA‐DPB1 polymorphism in Nu ethnic group of south‐west China

Abstract: In the present study, DNA typing for HLA-DPB1 was performed using polymerase chain reaction-sequencing-based typing method in 72 randomly selected Nu ethnic individuals inhabiting the Yunnan province of south-west China. Among the 12 detected DPB1 alleles, the most frequent was DPB1*1301, with the percentage of 20.83%, followed by DPB1*0501 (19.44%), DPB1*040101 (16.67%) and DPB1*2801 (9.72%). The allele DPB1*1501 was found for the first time in the Chinese population. Neighbour-joining showed that the Nu ethn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…The majority of studies have shown that DPB1 locus is not under balancing selection. The present study showed that homozygosity for DPB1 locus does not differ significantly from the value expected under neutrality, which is in concordance with other previously published results (19).…”
Section: Introductionsupporting
confidence: 94%
“…The majority of studies have shown that DPB1 locus is not under balancing selection. The present study showed that homozygosity for DPB1 locus does not differ significantly from the value expected under neutrality, which is in concordance with other previously published results (19).…”
Section: Introductionsupporting
confidence: 94%
“…DPB1*1301, the second frequent allele in Bais (13.28%), was also very common among many Southeast Asian populations. Likewise, the frequency of the DPB1*1301 in Chinese populations is also higher in southern Chinese populations (10.1%–33.3%) (13–17, 24–29) than in northern Chinese populations like Kazak (1.2%) (19), Shenyang Han (1.8%) (18), Man (2.1%) (20), Uygur (4.4%) (22) and Northern Han (5.1%) (21). DPB1*020101 and DPB1*040101, being the two widely observed alleles all over the world, were also frequently observed in Bai, with frequencies of 10.93% and 9.77%, respectively.…”
Section: Allele Frequencies Of Hla‐drb1 ‐Dqb1 and ‐Dpb1 In The Bai Ementioning
confidence: 93%